2017
DOI: 10.13073/fpj-d-16-00027
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Radial Growth Rate on Wood Properties and Anatomical Characteristics and an Evaluation of the Xylem Maturation Process in a Tropical Fast-Growing Tree Species, Gmelina arborea

Abstract: The aim of this study was to evaluate the effects of radial growth on wood properties and anatomical characteristics and to clarify the xylem maturation process in Gmelina arborea. Stem diameter, tree height, and stress-wave velocity were investigated for 54 5-year-old G. arborea trees planted in Indonesia. In addition, radial variations of wood properties (basic density and compressive strength parallel to the grain in green condition) and anatomical characteristics (fiber and vessel morphologies) were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…On the other hand, in broad-leaved tree species growing in the tropics and sub-tropics, anatomical characteristics, and physical and mechanical properties of secondary xylem stabilize in relation to 1) distance from the pith or 2) cambial age (Wiemann and Williamson 1988;Honjo et al 2005;Kojima et al 2009c;Lachenbruch et al 2011). The maturation depending on diameter growth has been found in many fast-growing tree species, such as Acacia spp., Azadirachta excelsa, Casuarina equisetifolia, Gmelina arborea, Neolamarckia cadamba, Ochroma pyramidale, and Falcataria falcata (Wiemann and Williamson 1988;Honjo et al 2005;Chowdhury et al 2009;Kojima et al 2009a, b, c;Wahyudi et al 2014Wahyudi et al , 2016Ishiguri et al 2016;Hidayati et al 2017;Pertiwi et al 2018Pertiwi et al , 2022. On the other hand, several tree species with slower growth such as Shorea spp.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in broad-leaved tree species growing in the tropics and sub-tropics, anatomical characteristics, and physical and mechanical properties of secondary xylem stabilize in relation to 1) distance from the pith or 2) cambial age (Wiemann and Williamson 1988;Honjo et al 2005;Kojima et al 2009c;Lachenbruch et al 2011). The maturation depending on diameter growth has been found in many fast-growing tree species, such as Acacia spp., Azadirachta excelsa, Casuarina equisetifolia, Gmelina arborea, Neolamarckia cadamba, Ochroma pyramidale, and Falcataria falcata (Wiemann and Williamson 1988;Honjo et al 2005;Chowdhury et al 2009;Kojima et al 2009a, b, c;Wahyudi et al 2014Wahyudi et al , 2016Ishiguri et al 2016;Hidayati et al 2017;Pertiwi et al 2018Pertiwi et al , 2022. On the other hand, several tree species with slower growth such as Shorea spp.…”
Section: Introductionmentioning
confidence: 99%
“…Zobel and van Buijtenen (1989) reviewed the relationships between radial growth rate and wood density in hardwoods; there is no apparent relationships in diffuse-porous wood, while increase of growth ring width resulted in increase of wood density in ring-porous wood. Many researchers also focused on the relationships in fast-growing tree species grown in tropical countries (Ohbayashi & Shiokura 1990, DeBell et al 2001, Wahyudi et al 2001, Kojima et al 2009a,b, Makino et al 2012, Pillai et al 2013, Hidayati et al 2017, Pertiwi et al 2017a,b, 2018. Kojima et al (2009b) showed that high growth rates did not intrinsically affect the wood properties of fast-growing tropical or subtropical species that has reached harvesting age.…”
Section: Introductionmentioning
confidence: 99%
“…Wood properties have been investigated for several fast-growing tree species planted in Indonesia, such as F. moluccana (Ishiguri et al 2007;Fajriani et al 2013), Gmelina arborea (Kim et al 2012;Hidayati et al 2017), and A. cadamba (Fajriani et al 2013;Seo et al 2015;Pertiwi et al 2017). However, available information is limited on the wood properties of other fast-growing tree species grown in the community forest in Indonesia.…”
Section: Introductionmentioning
confidence: 99%